Is Being a Lark Healthier for Patients with Type 1 Diabetes Mellitus? - Valiensi, Stella Maris; Folgueira, Agustín Leandro; Diez, Joaquin Jose; Gonzalez-Cardozo, Agustin; Vera, Vanesa Antonella; Camji, Julieta Marina; Alvarez, Adriana Mabel (Sleep Science, 2023)
Background Sleep quality and mood have been evaluated in type 1 diabetic (T1DM) patients, but chronotypes were not studied. Our objectives were to analyze chronotypes, sleep and mood variables and to describe their association with some metabolic variables in this population.Methods An observational, cross-sectional study was performed. Adults with a diagnosis of T1DM were included. We evaluated chronotypes by the Morningness-Eveningness Questionnaires, sleep quality by Pittsburgh Sleep Quality Index (PSQI), excessive daytime sleepiness by Epworth Sleepiness Scale (ESS), symptoms of depression by Patient Health Questionnaire - 9 (PHQ-9) and emotional well-being by Emotional Well Being Index (IWHO-5). A few metabolic variables were included.Results Ninety-five patients participated. The mean age was 38 years old (range 18–70). The average body mass index (BMI) was 24.4 Kg/m2 (standard deviation [SD]: 4.6). Out of the total sample, 52.6% were males. The Intermediate chronotype was predominant: n = 56 (55%). We found poor quality of sleep in 67.4% of the sample, excessive daytime sleepiness in 14.7%, depressive symptoms in 6.3% by PHQ9 and low perception of well-being by IWHO-5 in 16.8%. Evening chronotype scored worse in sleep quality (p = 0.05) and had lower well-being (p = 0.03) compared with the other chronotypes. Higher MEQ values (morningness) correlated with lower height (p = 0.043), lower values in the PSQI (p = 0.021); and higher values in emotional well-being (p = 0.040).Conclusions We found that the predominant chronotype in T1DM was the intermediate. Two-thirds reported poor quality of sleep and 14,7% excessive daytime sleepiness. Possible diagnosis of a depressive disorder in 6.3% and poor self-perception of emotional well-being in 16. 8% were observed. The morning chronotype had significant correlation with better sleep quality and higher scores in emotional well-being.
Keywords: sleep; depression; type 1 diabetes mellitus; sleepiness